Alternative Acetate Production Pathways in Chlamydomonas reinhardtii during Dark Anoxia and the Dominant Role of Chloroplasts in Fermentative Acetate Production. Issue 11 (7th November 2014) - Yang, Wenqiang; Catalanotti, Claudia; D'Adamo, Sarah; Wittkopp, Tyler M.; Ingram-Smith, Cheryl J.; Mackinder, Luke; Miller, Tarryn E.; Heuberger, Adam L.; Peers, Graham; Smith, Kerry S.; Jonikas, Martin C.; Grossman, Arthur R.; et al.
Abstract : Acetate is a primary Chlamydomonas fermentative product and is linked to dark, anoxic ATP biosynthesis. Chlamydomonas ack / pat mutants were isolated to further characterize fermentation networks, revealing that chloroplast pathways are dominant in this alga, and that despite blocking the primary ATP-generating routes to acetate, Chlamydomonas retains the metabolic flexibility to produce acetate. Abstract: Chlamydomonas reinhardtii insertion mutants disrupted for genes encoding acetate kinases (EC 2.7.2.1) (ACK1 and ACK2) and a phosphate acetyltransferase (EC 2.3.1.8) (PAT2, but not PAT1) were isolated to characterize fermentative acetate production. ACK1 and PAT2 were localized to chloroplasts, while ACK2 and PAT1 were shown to be in mitochondria. Characterization of the mutants showed that PAT2 and ACK1 activity in chloroplasts plays a dominant role (relative to ACK2 and PAT1 in mitochondria) in producing acetate under dark, anoxic conditions and, surprisingly, also suggested that Chlamydomonas has other pathways that generate acetate in the absence of ACK activity. We identified a number of proteins associated with alternative pathways for acetate production that are encoded on the Chlamydomonas genome. Furthermore, we observed that only modest alterations in the accumulation of fermentative products occurred in the ack1, ack2, and ack1 ack2 mutants, which contrasts with the substantial metabolite alterations described in strains devoid of other key fermentation enzymes.